DETERMINANTS OF ACADEMIC PERFORMANCE AMONG MATURE ENTRY STUDENTS: A CASE OF NAKURU AND NAIROBI CAMPUSES OF KENYA METHODIST UNIVERSITY - KARINGA, MUNUHE PATRICK; Kathuri, Prof. N.J.; Njagi, Dr. Zachary (IJRDO- Journal of Educational Research, 2018)
Globally, universities are recording a greater mix of students currently more than in the past. The purpose of the study was to investigate the social factors and how it impacts on academic performance among mature age entry students. The study was guided by the Needs theory by Abraham Maslow and adopted descriptive survey research design. The total target population was all the 289 mature age entry students enrolled at Nakuru and Nairobi campuses of Kenya Methodist University, administrators, Chairmen of Departments and lecturers of the two campuses. Convenient sampling was applied to obtain a sample size of 100 mature age entry students who participated in the study. University administrators were purposefully sampled based on the information required for the study. Questionnaire and interview schedules were used for collecting data for the study. In the study, the researcher carried out a pilot study and then carefully analyzed the results for clarity, correctness and also ensured that the items were comprehensive as far as the coverage of objectives was concerned. In order to ensure smooth research procedures, various ethical issues such as anonymity, confidentiality and informed consent were observed. The data from the questionnaires were edited, coded and entered into the computer for analysis. Both qualitative and quantitative methods were used in analyzing the data using Statistical Package for Social Sciences version 23 using both descriptive and inferential statistics. Results are presented in tables and charts to enhance clarity. Finally, the study found out that current engagement, inability to fit in university programmes and inability to balance demands of mature age entry students affect their academic performance. The universities should develop academic programmes that help reduce conflict that mature age students’ encounter with their jobs and family commitments. This would involve revising the calendar for this category of students and also introduce weekend and evening classes where possible.